The Effect of Entrepreneurship and Self-Efficacy on Entrepreneurial Interest Through Locus of Control as An Intervening Variable - Purwantiningsih, Estu Setyo; Wardoyo, Cipto; Wardana, Ludi Wishnu (Journal of Applied Business, Taxation and Economics Research, 2025)
This research aims to assess students' interest in entrepreneurship. In this study, the locus of control serves as a mediator between entrepreneurship, self-efficacy, and entrepreneurial satisfaction. This research is based on multiple prior studies. The participants are students from public service colleges with fashion businesses in Mojokerto, specifically from SMKN 1 Sooko and SMKN Jatirejo, who are studying commerce in the eleventh and twelfth grades of the fashion department. The sample consists of 237 students who took part in an online survey, and the data was analyzed using linear regression modeling (PLS-SEM). The findings indicate that entrepreneurship and self-efficacy positively impact job satisfaction through the management environment.